The association of snoring, growth, and metabolic risk factors at the age of two years - Maija Katila; Anna-Liisa Satomaa; Sari-Leena Himanen; Marja-Terttu Saha; Nina Vuorela; Tiina Paunio; E. Juulia Paavonen; Outi Saarenpää-Heikkilä (Sleep Science and Practice)
Abstract Background and aims This observational study examined the association of snoring and growth during early childhood and the cardiovascular and metabolic risk factors based on blood samples at the age of two years. Methods and results The sample comprised 78 children from the CHILD-SLEEP birth cohort with full-night polysomnography (PSG) and a questionnaire consisting of parts concerning the child's sleep and environmental factors at 24 months. The growth charts were collected from well-baby clinics. Metabolic blood samples were drawn from 31 children. There were no statistically significant differences in the growth parameters of snoring children compared to controls during the first two years of life. However, in linear regression models, snoring time in PSG significantly predicted lower levels of HDL (β = -0.484, p = 0.007) and ApoA1 (β = -0.451, p = 0.049) and higher levels of hs-CRP (β = 0.410, p = 0.019). Conclusion In conclusion, in Finnish children the levels of HDL and ApoA1 were inversely related to the snoring time in PSG. In addition, the snoring time in PSG significantly predicted higher levels of hs-CRP. These results suggest that snoring in early childhood could negatively alter the serum metabolic profile, adding to the risk of cardiovascular diseases in adulthood.